An experience of crisis intervention in southern Peru: Psychological Brigades - Kudó, Inés (2005)
This paper summarizes the experience of the Psychological Brigades conducted in 2001 in response to an earthquake that battered the southern part of the country, causing countless human and material losses and leaving over 200 thousand victims. The brigades gathered about 100 people among faculty members, students and graduated students from the Department of Psychology of the Pontificia Universidad Católica del Perú, who went to the affected areas to provide psychological support. The complete intervention is presented, including the design previous to the intervention, techniques used during the intervention and the evaluation of the results. These include the impact on the assisted population, the factors that contributed to the intervention success, as well as the impact on the brigades’ members. The assisted population specially remarks the value of feeling heard and accompanied, and of having a space to talk and meditate about its experience, fears and fantasies.